Biochar effect on crop performance and Pb and Zn uptake of tomato (Solanum lycopersicum, L.) plants grown on heavy metals contaminated Kosovo soils. Issue 9 (1st September 2020) - Voca, Hana; Piscitelli, Lea; Mezzapesa, Giuseppe Natale; Mondelli, Donato; Miano, Teodoro; D'Orazio, Valeria
Abstract: A greenhouse pot experiment was conducted to evaluate the effect of biochar on the growth and uptake of Pb and Zn by tomato plants ( Solanum lycopersicum, L.) cultivated in two highly contaminated Kosovo soils, A and B. Plants were cultivated in the biochar amended and unamended soils. As expected, the biochar addition to the two polluted soils has contributed to significantly improve the crop yields, in terms of both fresh and dry weight. Further, results indicated that the effect of biochar on metal mobility is closely related, besides its properties, to soil's native characteristics. In fact, the addition of biochar to soil B had also beneficial effects on the uptake of both metals, halving in some cases the values of the biological accumulation and transfer coefficients, while it did not show the same efficacy on soil A.